Addressing the Regulatory Gaps in Indonesian Financial Alternative Dispute Resolution - Keumala, Dinda; Setiyono, Setiyono; Ikhwan bin Mohd Zain, Muhamad (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
This study examines the regulatory gaps in Indonesia’s Alternative Dispute Resolution Institution (LAPS SJK), established by the Indonesian Financial Services Authority (OJK) to resolve disputes between consumers and financial service providers. Using a normative method, the study identifies significant shortcomings in the legal framework governing LAPS SJK. Specifically, the founding of LAPS SJK did not explicitly reference the Law of OJK and its amendments. Moreover, the OJK regulation governing the institution fails to account for the Law on Arbitration and Alternative Dispute Resolution Institutions, leading to inconsistencies in the legal foundation. Additionally, the terminology used in OJK regulations diverges from the Law on the Development and Strengthening of the Financial Sector. This research highlights the need for a more coherent and comprehensive legal framework for financial services dispute resolution in Indonesia.